An Analysis of Dispute Resolution Mechanisms in the Islamic Banking and Finance Industry in Malaysia - Aishat Abdul-Qadir Zubair (Jurnal Hukum Novelty, 2020)
Introduction to The Problem: With the increasing boost to the Malaysian Islamic finance industry and the sophistication experienced in the industry with regards to product development, there is a substantial downside of such enviable achievements, which is the gradual surge in the number of disputes involving Sharia-compliant transactions. It is therefore important to analyse the existing dispute resolution mechanisms in the Islamic finance industry in Malaysia.Purpose/Objective Study: The article aims to analyse the court system as a dispute resolution mechanism as well as the other alternative dispute resolution mechanisms available to parties in resolving the dispute in the Islamic banking and finance industry in Malaysia.Â Design/Methodology/Approach: This study adopts a doctrinal legal method in examining the relevant Islamic dispute resolution mechanisms that are unique to Islamic finance disputes.Findings: The findings of this research reveal that some issues are causing untold hardships on parties in Islamic finance contractual disputes with the present jurisdiction of the courts in Malaysia. It is in line with the hypothesis of the research that the continued preference for litigation as a means of settling disputes in the Islamic finance industry is not sustainable due to the paradigm shift in dispute resolution involving financial matters globally.Paper Type: Research Article